B-Track: A model for assisting in non-communicable diseases through human behavior analysis - Dias, Lucas Pfeiffer Salomão; Barbosa, Jorge Luis Victória (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
Chronic diseases are among 7 out of the 10 leading causes of death worldwide. The main chronic diseases are heart disease, cancer, chronic respiratory diseases, and diabetes. Heart disease alone causes 9 million deaths a year. Lifestyle changes can prevent many chronic diseases’ deaths and their risk factors. In addition, machine learning and wearable devices have been used for behavior analysis. Therefore, this research proposes B-Track, a computational model for assistance in chronic disease care through analyzing behaviors that attenuate or worsen the risk factors associated with chronic diseases, working with user behavior profiles and recommendations for healthier behaviors. Besides, an ontology was created to be used as a knowledge model for the B-Track model to track behaviors associated with risk factors for chronic diseases. The B-Track collects data from different data sources for current and future human behavior analysis through the usage of data fusion and machine learning models. These data comprise the patients’ context histories, which include sensor data and data from self-management surveys. Based on the ontology inferences, the B-Track acts in a personalized manner, sending recommendations for habit changes to patients and allowing user accompaniment by health professionals. The scientific contribution of B-Track model is the analysis of human behaviors directly associated with risk factors and their susceptibility to the development of chronic diseases. The model was evaluated through a prototype, which was used by 10 patients during their treatment. Patients participating in the experiment had habits associated with risk factors with susceptibility to developing coronary heart disease, diabetes, and dementia. Some of these patients already had heart disease, hypertension, or diabetes. Patients P4, P5, P6, P7, and P8 showed positive changes in their behaviors in the long term, where P4 increased their consumption of healthy foods, P5 started exercising with highest frequency, and P6, P7, and P8 also made positive changes to their exercise habits. Patient P1 showed no changes, and the others had only shorter-term improvements. Overall, the TAM evaluation showed that B-Track model was useful to 83% of patients, and 80% of the patients found the model easy to use.